Axonal Stimulations With a Higher Frequency Generate More Randomness in Neuronal Firing Rather Than Increase Firing Rates in Rat Hippocampus - Wang, Zhaoxiang; Feng, Zhouyan; Wei, Xuefeng (Frontiers in Neuroscience, 2018)
Deep brain stimulation (DBS) has been used for treating many brain disorders. Clinical applications of DBS commonly require high-frequency stimulations (HFS, ~100 Hz) of electrical pulses to obtain therapeutic efficacy. It is not clear whether the electrical power of HFS functions other than generating firing of action potentials in neuronal elements. To address the question, we investigated the reactions of downstream neurons to pulse sequences with a frequency in the range 50 – 200 Hz at afferent axon fibers in the hippocampal CA1 region of anaesthetized rats. The results show that the mean rates of neuronal firing induced by axonal HFS were similar even for an up to four-fold difference (200:50) in the number and thereby in the power of electrical pulses delivered. However, HFS with a higher pulse frequency (100 or 200 Hz) generated more randomness in the firing pattern of neurons than a lower pulse frequency (50 Hz), which were quantitatively evaluated by the significant changes of two indexes, namely the peak coefficients and the duty ratios of excitatory phase of neuronal firing, induced by different frequencies (50 - 200 Hz). The findings indicate that a large portion of the HFS power might function to generate a desynchronization effect through a possible mechanism of intermittent depolarization block of neuronal membranes. The present study addresses the demand of high frequency for generating HFS-induced desynchronization in neuronal activity, which may play important roles in DBS therapy.